1983
DOI: 10.1139/g83-025
|View full text |Cite
|
Sign up to set email alerts
|

The characterization of a mutant affecting DNA metabolism in the development of D. melanogaster

Abstract: Using a "single-fly" nucleic acid hybridization method, we have surveyed a collection of D. melanogaster strains in search of variants which affect DNA complementary to the polypyrimidine sequence corresponding to one strand of the 1.705 satellite. Hybridization of labelled polypyrimidine probe to polypurine sequence in nucleic acid extracts of single flies, followed by thermal chromatography over hydroxyapatite led to the identification of one variant. The strain Cy/M(2)S2(10) produced excess hybrid, much of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 4 publications
2
5
0
Order By: Relevance
“…This observation was consistent with the previously described phenotype of the DNase 1 lmh mutant (which unfortunately no longer exists) that was shown to accumulate DNA molecules on the order of f 200 bp in length (Stone et al, 1983). This accumulation was found to be ubiquitous, although mature ovaries accumulated DNA at a relatively higher rate with DNA-containing vesicles found near the chorionic appendages of oocytes and in the lateral oviducts (Stone et al, 1983). It was suggested that the presence of this low-molecular-weight DNA was the result of deficient degradation of nurse cell nuclei during oocyte maturation (Stone et al, 1983;Mukae et al, 2002).…”
Section: Melanogastersupporting
confidence: 92%
See 2 more Smart Citations
“…This observation was consistent with the previously described phenotype of the DNase 1 lmh mutant (which unfortunately no longer exists) that was shown to accumulate DNA molecules on the order of f 200 bp in length (Stone et al, 1983). This accumulation was found to be ubiquitous, although mature ovaries accumulated DNA at a relatively higher rate with DNA-containing vesicles found near the chorionic appendages of oocytes and in the lateral oviducts (Stone et al, 1983). It was suggested that the presence of this low-molecular-weight DNA was the result of deficient degradation of nurse cell nuclei during oocyte maturation (Stone et al, 1983;Mukae et al, 2002).…”
Section: Melanogastersupporting
confidence: 92%
“…In mutants deficient for both enzymes, again no laddering was observed (Mukae et al, 2002). These observations indicate a mechanism of DNA degradation similar to that proposed by Stone et al (1983), where dCAD is required to generate lowmolecular-weight nucleosomal multimers and DNase II functions to remove this DNA (Fig. 4).…”
Section: Melanogastersupporting
confidence: 75%
See 1 more Smart Citation
“…These results indicated that CAD and DNase II work independently to degrade the chromosomal DNA during embryogenesis and oogenesis. Stone et al (1983) previously detected Feulgen-positive materials in the egg chambers of the Cy/M(2)S2 lo Drosophila strain, which they found to carry a hypomorphic allele of the gene affected by the DNase-1 lo mutation, that is, DNase II. In fact, the ovaries of DNase-1 lo flies showed materials that could be strongly stained with acridine orange in the dorsal appendage of the mature eggs (Fig.…”
Section: ) P(l(2)k00617)-p(228) (Lane 2) P(228) (Lane 3) P(228)-p(mentioning
confidence: 99%
“…By hybridizing a labeled polypyrimidine probe to DNA from DNase-1 lo flies, Stone et al (1983) detected a low-melt hybrid with low thermal stability in the ovaries and proposed a two-step model for the degradation of nurse cell nuclei. In the first step, DNA is degraded into AT-rich DNA fragments of <200 bp, and these fragments are further digested to oligo-or mononucleotides by acid DNase in the second step.…”
Section: Genes and Development 2667mentioning
confidence: 99%